Comparison of Electrolyte Profile between Malnourished andWellNourished Diarrhoeal Children (The Planet, 2024)
Introduction: Diarrhea remains a leading cause of morbidity and mortality in children, which depends on the nutritional status of the population. Malnutrition exacerbates the severity of diarrheal illnesses and impairs the body’s ability to recover. This study aimed to compare electrolyte profiles between malnourished and well-nourished diarrhoeal children. Methods & Materials: This prospective observational study was conducted at Sher-E-Bangla Medical College Hospital, Barisal, Bangladesh, from January 2023 to January 2024. A total of 60 children presenting with diarrhea were enrolled, including 30 malnourished and 30 well-nourished children. Analysis was done using (SPSS) Statistical Package for Social Sciences. Descriptive statistics were used to summarize categorical data. Result: The highest incidence of malnutrition was observed in children aged 1–3 years (50.0%), while the majority of well-nourished children were in the 6 months to 1-year age group (47.0%). Gender distribution was equal, with 67.0% males in both groups. Sodium levels were mostly normal in both groups, but malnourished children had 10.0% hypernatremia and 3.0% hyponatremia. Potassium levels were more balanced in well-nourished children, with 50.0% of malnourished children showing hypokalemia. Chloride levels were above normal in 50.0% of malnourished children, compared to 57.0% in well-nourished children. In terms of feeding practices, 93.0% of malnourished children had improper feeding practices, while all well-nourished children had normal feeding practices. Conclusion: Malnourished children are more likely to experience severe electrolyte imbalances, which can complicate the clinical course of diarrhea and increase the risk of dehydration. The high incidence of improper feeding practices in malnourished children further exacerbates these issues, underlining the importance of appropriate feeding and rehydration strategies.
Keywords: Electrolyte Profile; Nutritional status; Diarrhea; Dehydration